Chemical profile and bioprospecting of cocoa beans analyzed by paper spray mass spectrometry (Research, Society and Development, 2020)
The quality cocoa derived products have increasingly received greater recognition and relevance both by consumers and producers. Cocoa beans are the main components responsible for much of the cocoa agro-industrial chain being currently valued for the bioactive properties found in the species' by-products, creating a great interest in exploring the potentials of cocoa. Much of the work that aims to evaluate the compounds found in the fruit's beans employ HPLC, UHPLC and LC-MS. In this work Paper Spray Mass Spectrometry (PS-MS) was employed as a method for characterizing and bioprospecting the chemical profile of cocoa beans (Theobroma cacao) of the forrasteiro variety grown in the Trans-Amazonian region of the Brazilian State of Pará. Methanolic extracts were prepared from samples of cocoa beans and evaluated in the negative and positive ionization modes. In the positive ionization mode it was possible to identify 11 compounds, comprising the classes of methylxanthines (18.2%), phenylpropanoids (9.1%), steroids (27.3%) and flavonoids (45.5%), while in the negative ionization mode, it was possible to identify 55 compounds among hydroxybenzoic acids (16.4%), phenylpropanoids (20.0%), flavonoids (52.7%), sugars and glycosides (10.9%). PS-MS proved to be an effective method for the evaluation of cocoa bean samples, being able to identify a total of sixty-six compounds. The bioactive properties attributed to cocoa were confirmed in the samples analyzed by the compounds identified through PS-MS whilst also indicating the quality of the raw material and describing its chemical profile, contributing to a greater understanding of its attributes.